Hot melt adhesive for non-asphalt-based waterproof coiled material as well as preparation method and application of hot melt adhesive
By preparing hot melt adhesives of raw materials such as polymer polyols, isocyanates, and combining the hydrophobic effects of shellac and EVA, the problems of non-asphalt waterproof coil hot melt adhesives becoming brittle at low temperatures, decreasing adhesion force at high temperatures and wind and rain erosion are solved. High weather resistance and toughness are achieved and service life is extended.
Patent Information
- Application Number
- CN202411470324.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-27
AI Technical Summary
The hot melt adhesive of non-asphalt waterproof coils is prone to become brittle and cracking in low temperature environments, and the adhesion force decreases at high temperatures, and it is easy to cause edge lifting under typhoons and rainwater to wash, affecting service life.
Hot melt adhesive prepared with raw materials such as polymer polyols, isocyanates, acrylic resins, EVA, shellac carrier fibers and filler particles can improve the weather resistance, toughness and stickiness of hot melt adhesives through the combination of crosslinking and viscosity enhancer. knot stability and harness the hydrophobic effects of shellac and EVA to resist wind and rain erosion.
It extends the service life of the waterproof coil, improves the adhesion and toughness of hot melt adhesive, prevents edges from being raised, and enhances resistance to wind and rain erosion.
Smart Images

Figure BDA0005094512550000071 
Figure BDA0005094512550000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of hot melt adhesives, and more specifically, to a hot melt adhesive for non-asphalt-based waterproofing membranes and a preparation method thereof. Background Art
[0002] Non-asphalt waterproofing membrane is a kind of waterproof material. Compared with traditional asphalt waterproofing membrane, it has higher performance and longer service life. Non-asphalt waterproofing membrane is generally made of polymer materials, such as high-density polyethylene, polyvinyl chloride, etc. These polymer materials have excellent weather resistance, corrosion resistance and wear resistance, and can effectively resist the erosion of the external environment and ensure the service life of the waterproofing membrane.
[0003] Non-asphalt waterproofing membranes are generally used in waterproofing projects such as roofs, walls and basements in the construction industry. After the non-asphalt waterproofing membrane is laid on the roof, the low temperature of the external environment can easily cause the hot melt adhesive of the waterproofing membrane to become brittle and crack, while the high temperature of the external environment can easily cause the hot melt adhesive of the waterproofing membrane to age and reduce its adhesion. In addition, when encountering typhoons and rainy weather, with the intensification of wind force and the erosion of rain, the adhesion of the hot melt adhesive on the non-asphalt waterproofing membrane can easily decrease, resulting in poor bonding between the hot melt adhesive and the concrete on the roof, and even the edge of the non-asphalt waterproofing membrane may be directly lifted up, affecting the service life of the waterproofing membrane.
[0004] Therefore, how to prepare a new hot melt adhesive that has the advantages of strong weather resistance, good toughness, and not easy to crack, and also has the advantage of strong adhesion under typhoon and rain erosion conditions, ensuring that the edges are not easily lifted up by wind and rain erosion, thereby extending the service life of the waterproof membrane, is a problem to be solved. Summary of the invention
[0005] In order to prepare a new hot melt adhesive which has the advantages of strong weather resistance, good toughness and not easy to crack, and under the conditions of typhoon and rain scouring, the hot melt adhesive also has the advantage of strong adhesion to ensure that the edge is not easily lifted up by wind and rain scouring, thereby extending the service life of the waterproof membrane, the present application provides a hot melt adhesive for non-asphalt-based waterproof membrane and a preparation method thereof.
[0006] In the first aspect, the present application provides a hot melt adhesive for non-asphalt-based waterproof membranes, adopting the following technical scheme: a hot melt adhesive for non-asphalt-based waterproof membranes, the hot melt adhesive comprising the following raw materials in parts by weight: 70-100 parts of polymer polyol, 30-50 parts of isocyanate, 20-30 parts of acrylic resin, 20-30 parts of EVA, 10-20 parts of chain extender, 5-10 parts of compatibilizer, 5-15 parts of shellac carrier fiber, 10-20 parts of filling particles, and 2-5 parts of antioxidant.
[0007] By adopting the above technical scheme, polymer polyol and isocyanate are combined to obtain PUR hot melt adhesive, which has the advantages of water resistance, temperature resistance and chemical resistance. It is combined with acrylic resin and EVA to further improve the weather resistance, flexibility and viscosity of the hot melt adhesive. The cross-linking effect of the chain extender and the compatible adhesion between the raw materials by the compatibilizer are further improved to further improve the cross-linking and bonding effect between the shellac carrier fibers and filling particles and the polymer polyol and EVA, thereby further improving the weather resistance, toughness and bonding stability of the hot melt adhesive.
[0008] Acrylic resin and EVA are combined to have high viscosity, and the larger surface area of shellac-loaded fibers and the bonding effect of shellac further improve the viscosity of the hot melt adhesive. The filling effect of the filling particles improves the bonding stability and strength of the hot melt adhesive, and the hot melt adhesive on the waterproof membrane is not easily peeled off or cracked due to wind. In addition, shellac, EVA and other materials have good waterproof effects and can further resist the erosion of the hot melt adhesive by typhoon-carried rainwater, so that the edge of the hot melt adhesive on the waterproof membrane is not easily lifted up by wind and rain, thereby extending the service life of the waterproof membrane.
[0009] Preferably, the shellac carrier fiber is prepared by bonding the surface of shellac particles with polycaprolactone melt and then bonding with polyimide fibers; the mass ratio of shellac particles, polycaprolactone melt and polyimide fibers is 1:0.3-0.6:1-2.
[0010] By adopting the above technical scheme, the viscosity of the polycaprolactone melt is utilized to adhere the polyimide fiber to the surface of the shellac particles, so that the polyimide fiber forms a fiber support network around the shellac particles. The polyimide fiber has high flexibility, which is not only convenient for adhering to the surface of the shellac particles, but also can improve the flexibility of the hot melt adhesive and resist the impact of typhoons. In addition, the polycaprolactone, shellac particles and polyimide fibers all have good hydrophobic and waterproof effects, which can further resist the erosion of the hot melt adhesive on the waterproof membrane by typhoons and rainy weather, ensure the adhesion stability of the hot melt adhesive on the roof concrete, and prevent the problem of edge lifting, thereby extending the service life of the waterproof membrane.
[0011] When the hot melt adhesive on the waterproof membrane comes into contact with the roof concrete, even if the concrete surface has been cleaned, it is inevitable that there will be all kinds of dust particles and other substances. During the compaction process, after the dust particles and other substances come into contact with the shellac carrier fibers, the fiber network on the surface is convenient for binding the dust particles, and the hot melt temperature is used to facilitate the hot melting of the shellac particles. After the shellac is hot-melted, it is easy to adhere to the dust particles, so that the dust particles are wrapped and it is not easy to affect the bonding effect between the hot melt adhesive and the concrete surface. If the dust particles are blocked between the hot melt adhesive and the concrete, the hot melt adhesive is easy to separate from the concrete surface under the erosion of wind and rain, affecting the adhesion stability of the waterproof membrane on the roof concrete. Therefore, by binding and wrapping the dust particles, the structure of shellac and polycaprolactone around the dust particles is realized, ensuring that the hot melt adhesive still has a high adhesion effect on the roof concrete surface where some dust particles exist, and it is not easy for the hot melt adhesive to separate from the concrete due to typhoons and rain erosion, thereby ensuring that the edge of the waterproof membrane is not easy to be lifted, thereby extending the service life of the waterproof membrane.
[0012] Preferably, the polyimide fiber is made of polyimide fiber filaments, rosin resin melt and silica gel particles in a mass ratio of 1:0.05-0.1:0.1-0.2.
[0013] By adopting the above technical scheme, the viscosity of the rosin resin melt is utilized to facilitate the adhesion of the silica gel particles to the surface of the polyimide fiber filaments, and the self-adhesive effect of the silica gel particles is utilized in combination with the surface self-adhesiveness of the rosin resin to facilitate the binding of dust particles on the concrete surface, so that the particulate matter on the concrete surface can be gradually bound by the polyimide fibers, and the flow coating effect of shellac and polycaprolactone after hot melting makes it difficult for the particulate matter to be separated between the hot melt adhesive and the concrete and affect the adhesion effect of the hot melt adhesive, thereby improving the adhesion stability of the hot melt adhesive on the concrete surface of the non-asphalt-based waterproof membrane, and not easily affecting the service life of the waterproof membrane on the roof concrete due to typhoons and rain erosion.
[0014] Preferably, the silica gel particles are prepared by treating silica gel microparticles with a silane coupling agent KH-570.
[0015] By adopting the above technical solution, after the silica gel particles are treated with the silane coupling agent KH-570, the silica gel particles have a certain waterproof and hydrophobic effect. Combined with the hydrophobicity of shellac and the hydrophobic effect of polycaprolactone, they can further block the moisture from the external environment and try to avoid the hot melt adhesive from being washed away from the roof concrete surface under typhoon and rain conditions, thereby ensuring the service life of the waterproof membrane.
[0016] Preferably, the filling particles are composed of carbon fibers, nano-silicon dioxide and zinc oxide whiskers in a mass ratio of 1:0.5-1:0.1-0.2.
[0017] By adopting the above technical scheme, carbon fiber, nano-silica and zinc oxide whiskers are matched, and the filling effect of carbon fiber and nano-silica is utilized to improve the stability and toughness of the hot melt adhesive, so that it can resist the erosion of wind and rain and is not prone to peeling off from the concrete surface. In addition, the thorny structure of zinc oxide whiskers is combined to further resist wind impact, and by buffering the impact force, it resists the influence of high wind and rain on the adhesion stability of the hot melt adhesive, thereby ensuring the service life of the non-asphalt-based waterproof membrane on the roof concrete.
[0018] Preferably, the chain extender consists of dopamine and polyethylene glycol in a mass ratio of 1:1-3.
[0019] By adopting the above technical scheme, dopamine and polyethylene glycol are combined, and the amino group of dopamine and the hydroxyl group of polyethylene glycol are combined with the hydroxyl group of the polymer polyol to improve the cross-linking structure density of the hot melt adhesive, thereby improving the strength and toughness of the hot melt adhesive, ensuring that the hot melt adhesive on the waterproof membrane is stably adhered to the concrete surface while being able to resist external impacts, thereby extending the service life of the waterproof membrane.
[0020] Preferably, the compatibilizer is composed of maleic anhydride grafted EVA.
[0021] By adopting the above technical solution, maleic anhydride grafted EVA can improve the compatibility of EVA with other substances, improve the viscosity of the hot melt adhesive, and at the same time improve the flexibility of the hot melt adhesive, thereby ensuring that the hot melt adhesive is stably bonded to the concrete surface.
[0022] Preferably, the antioxidant is antioxidant 1010.
[0023] By adopting the above technical solution, the hot melt adhesive can have a good anti-oxidation effect and the edge lifting problem is not likely to occur, thereby ensuring that the non-asphalt-based waterproof membrane has a long service life on the roof concrete.
[0024] In a second aspect, the present application provides a method for preparing a hot melt adhesive for a non-asphalt-based waterproof membrane, using the following technical solution: A method for preparing a hot melt adhesive for a non-asphalt-based waterproofing membrane comprises the following steps: S1, weighing polymer polyol and isocyanate, mixing them evenly, heating them for reaction, then adding chain extender, and continuing the reaction to obtain a primary mixture; S2. Add acrylic resin, EVA, compatibilizer, fiber carrier shellac, filler particles and antioxidant to the primary mixture, mix and stir evenly, continue to react, and after defoaming, obtain the finished product.
[0025] By adopting the above technical scheme, the prepared hot melt adhesive has the advantages of strong weather resistance, good toughness and not easy to crack. In addition, under typhoon and rain scouring conditions, the hot melt adhesive also has the advantage of strong adhesion, ensuring that the edge is not easily lifted up by wind and rain scouring, thereby extending the service life of the waterproof membrane.
[0026] In a third aspect, the present application provides a non-asphalt waterproofing membrane, which adopts the following technical solution: A non-asphalt waterproofing membrane is made of a high-density polyethylene substrate and hot-melt adhesive.
[0027] By adopting the above technical scheme, the hot melt adhesive is adhered to the surface of the high-density polyethylene substrate, and the hot melt adhesive is curled and stacked after drying. When in use, the hot melt adhesive is heated to hot melt, and the waterproof membrane is adhered to the roof concrete surface by utilizing the viscosity of the hot melt adhesive, thereby achieving stable adhesion of the waterproof membrane; the waterproof membrane has the advantages of good weather resistance, good waterproofness, high tensile strength and high tear strength on the roof concrete surface, thereby extending the service life of the waterproof membrane on the concrete surface.
[0028] In summary, this application has the following beneficial effects: 1. PUR hot melt adhesive is obtained by combining polymer polyol and isocyanate, which has the advantages of water resistance, temperature resistance and chemical resistance. Combined with acrylic resin, EVA, shellac carrier fiber and filling particles, the hot melt adhesive has the advantages of strong weather resistance, good toughness and not easy to crack. In addition, under the conditions of typhoon and rain scouring, the hot melt adhesive also has the advantage of strong adhesion, ensuring that the edge is not easily lifted up by wind and rain scouring, thereby extending the service life of the waterproof membrane.
[0029] 2. The combination of polyimide fiber, shellac particles and polycaprolactone melt utilizes the self-adhesive effect of silica gel particles and the surface self-adhesiveness of rosin resin to bind dust particles on the concrete surface, so that the particulate matter on the concrete surface can be gradually bound by the polyimide fiber. Combined with the flow coating effect of shellac and polycaprolactone after hot melting, the particulate matter is not easily separated between the hot melt adhesive and the concrete and affects the adhesion effect of the hot melt adhesive, thereby improving the adhesion stability of the hot melt adhesive on the concrete surface of the non-asphalt-based waterproof membrane. Combined with the waterproofness of shellac and polycaprolactone, it is further ensured that the hot melt adhesive on the waterproof membrane is not easily affected by typhoons and rain erosion and affects the service life of the waterproof membrane on the roof concrete.
[0030] 3. The melting point of acrylic resin is generally around 105°C, the melting point of EVA is generally around 90°C, and the melting point of shellac is generally around 120°C. Therefore, in the hot-melt process of hot-melt adhesive, acrylic resin, EVA, and shellac can all play a bonding effect and bond to the concrete surface, ensuring that the hot-melt adhesive has a high adhesion stability on the concrete surface, while the polyimide fiber plays a filling and supporting effect, ensuring the strength and toughness of the waterproof membrane, ensuring that the waterproof membrane can resist the erosion of typhoons and rainwater, and extending the service life of the waterproof membrane on the roof concrete. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] The following raw materials are all commercially available.
[0033] Preparation Example of Shellac-Carrying Fiber Preparation Example 1: Shellac-loaded fiber is prepared by the following method: 1 kg of silica gel particles were placed in 10 kg of silane coupling agent KH-570 and stirred, ultrasonically dispersed at 20 kHz for 10 min, and the silica gel particles were separated by filtration to obtain silica gel particles; 0.1 kg of rosin resin melt is evenly sprayed on the surface of 1 kg of polyimide fiber, and then 0.15 kg of silica gel particles are added, the average length of the polyimide fiber is 100 μm, the rosin resin melt is obtained by completely hot-melting the rosin resin under the condition of heating to 180° C., the average particle size of the silica gel particles is 10 μm, and the adding speed of the silica gel particles is 60 g / min. During the adding process, the polyimide fiber is continuously stirred at a speed of 120 r / min. After being evenly mixed, it is dispersed until the polyimide fiber threads do not stick to each other and agglomerate to obtain a finished polyimide fiber; 0.5 kg of polycaprolactone melt is evenly sprayed on the surface of 1 kg of shellac particles, and then 1.5 kg of polyimide fiber is bonded. The average particle size of the shellac particles is 60 μm. The polycaprolactone melt is obtained by completely hot-melting polycaprolactone heated to 70°C. The adding rate of the polyimide fiber is 60 g / min. During the adding process, the shellac particles are continuously stirred at a speed of 120 r / min. After being evenly mixed, the shellac particles are dispersed until they do not stick to each other and agglomerate to obtain shellac carrier fibers.
[0034] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.05 kg of rosin resin melt was evenly sprayed on the surface of 1 kg of polyimide fiber, and then 0.1 kg of silica gel particles were added at a speed of 60 g / min. During the addition process, the polyimide fiber was continuously stirred at a speed of 120 r / min. After being evenly mixed, the polyimide fiber was dispersed until the polyimide fiber did not stick to each other and agglomerated, thereby obtaining a finished polyimide fiber; 0.3 kg of polycaprolactone melt is evenly sprayed on the surface of 1 kg of shellac particles, and then 1 kg of polyimide fiber is bonded. The addition rate of the polyimide fiber is 60 g / min. During the adding process, the shellac particles are continuously stirred at a speed of 120 r / min. After being evenly mixed, they are dispersed until the shellac particles do not stick to each other and agglomerate to obtain shellac carrier fibers.
[0035] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.1 kg of rosin resin melt was evenly sprayed on the surface of 1 kg of polyimide fiber, and then 0.2 kg of silica gel particles were added at a speed of 60 g / min. During the adding process, the polyimide fiber was continuously stirred at a speed of 120 r / min. After being evenly mixed, the polyimide fiber was dispersed until the polyimide fiber did not stick to each other and agglomerated, thereby obtaining a finished polyimide fiber; 0.6 kg of polycaprolactone melt is evenly sprayed on the surface of 1 kg of shellac particles, and then 2 kg of polyimide fiber is bonded. The addition rate of the polyimide fiber is 60 g / min. During the adding process, the shellac particles are continuously stirred at a speed of 120 r / min. After being evenly mixed, they are dispersed until the shellac particles do not stick to each other and agglomerate to obtain shellac carrier fibers. Example
[0036] Example 1: A hot melt adhesive for non-asphalt-based waterproofing membrane: 90kg polymer polyol, 40kg isocyanate, 25kg acrylic resin, 25kg EVA, 15kg chain extender, 8kg compatibilizer, 10kg fiber carrier shellac, 15kg filling particles, 3kg antioxidant; the polymer polyol is composed of polyether polyol and polyester polyol in a mass ratio of 1:1; the isocyanate is diisocyanate; the chain extender is composed of dopamine and polyethylene glycol in a mass ratio of 1:2; the compatibilizer is maleic anhydride grafted EVA; the fiber carrier shellac is the fiber carrier shellac prepared in Preparation Example 1; the filling particles are composed of carbon fiber, nano-silica and zinc oxide whiskers in a mass ratio of 1:0.85:0.15, the average length of the carbon fiber is 3μm, the average length of the nano-silica is 100nm, the zinc oxide whiskers are four-needle zinc oxide whiskers, and the average length of the needles is 10μm; the antioxidant is antioxidant 1010; The preparation method is as follows: S1. Weigh the polymer polyol and isocyanate, mix them evenly, react them at 120° C. for 30 min, then add the chain extender, and continue to react for 20 min to obtain a primary mixture; S2. Add acrylic resin, EVA, compatibilizer, chain extender, fiber carrier shellac, filler particles and antioxidant to the primary mixture, mix and stir evenly, continue to react for 30 minutes, and vacuum defoam to obtain the finished product.
[0037] Embodiment 2: This embodiment differs from Embodiment 1 in that: 70kg of polymer polyol, 30kg of isocyanate, 20kg of acrylic resin, 20kg of EVA, 10kg of chain extender, 5kg of compatibilizer, 5kg of fiber-carrying shellac, 10kg of filling particles, and 2kg of antioxidant; the chain extender consists of dopamine and polyethylene glycol in a mass ratio of 1:1; the fiber-carrying shellac is the fiber-carrying shellac prepared in Preparation Example 2; the filling particles consist of carbon fibers, nano-silicon dioxide and zinc oxide whiskers in a mass ratio of 1:0.5:0.1.
[0038] Embodiment 3: This embodiment differs from Embodiment 1 in that: 100kg polymer polyol, 50kg isocyanate, 30kg acrylic resin, 30kg EVA, 20kg chain extender, 10kg compatibilizer, 15kg fiber carrier shellac, 20kg filling particles, 5kg antioxidant; the chain extender consists of dopamine and polyethylene glycol in a mass ratio of 1:3; the fiber carrier shellac is the fiber carrier shellac prepared in Preparation Example 3; the filling particles consist of carbon fiber, nano-silicon dioxide and zinc oxide whiskers in a mass ratio of 1:1:0.2.
[0039] Embodiment 4: This embodiment differs from Embodiment 1 in that: In the preparation of shellac loaded fibers, the polyimide fibers were replaced by an equal mass of glass fibers.
[0040] Embodiment 5: This embodiment differs from Embodiment 1 in that: During the preparation of shellac-loaded fibers, polyimide fibers were replaced with polyimide filaments of equal mass.
[0041] Embodiment 6: This embodiment differs from Embodiment 1 in that: During the preparation of polyimide fibers for shellac-loaded fibers, silica gel particles are replaced with an equal mass of silica gel microparticles.
[0042] Embodiment 7: This embodiment differs from Embodiment 1 in that: No zinc oxide whiskers were added to the filler particles.
[0043] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No shellac-carrying fibers are added to the raw materials.
[0044] Comparative Example 2: The difference between this comparative example and Example 1 is that: The shellac carrier fibers are replaced by an equal mass of shellac in the raw material.
[0045] Comparative Example 3: The difference between this comparative example and Example 1 is that: The shellac carrier fibers are replaced by glass fibers of equal mass in the raw material, and the average length of the glass fibers is 80 μm.
[0046] Application Examples Application example 1: A non-asphalt waterproofing membrane: The hot melt adhesive is heated to 130°C and hot-melt bonded to the surface of a high-density polyethylene substrate. The average thickness of the high-density polyethylene substrate is 3 mm. The thickness of the hot melt adhesive layer formed after the hot melt adhesive is cooled and solidified is 2 mm, thereby obtaining a finished non-asphalt waterproof membrane. The hot melt adhesive is the hot melt adhesive prepared in Example 1.
[0047] Application Examples 2-7: The hot melt adhesives prepared in Examples 2-7 were used respectively.
[0048] Comparative Application Examples 1-3: The hot melt adhesives prepared in Application Examples 1-3 were used respectively.
[0049] Performance testing 1. Shear strength test The non-asphalt waterproof membrane was prepared by the preparation methods of Application Examples 1-7 and Comparative Application Examples 1-3 respectively. During the construction process, the hot melt method was adopted to heat the hot melt adhesive on the non-asphalt waterproof membrane to hot melt, and then covered the concrete surface. After rolling and compacting for 3 circles under a pressure of 20kg, it was allowed to stand for 48 hours, and then the shear strength of the hot melt adhesive on the concrete floor was tested with reference to GB / T7124-2008, and the data was recorded.
[0050] 2. Weather resistance test The non-asphalt waterproof membrane was prepared by the preparation methods of Application Examples 1-7 and Comparative Application Examples 1-3 respectively. During the construction process, the hot melt method was adopted to heat the hot melt adhesive on the non-asphalt waterproof membrane to hot melt, and then covered the concrete surface. After rolling and compacting for 3 circles under a pressure of 20 kg, it was left to stand for 48 hours, and then a 12-level typhoon wind force was simulated, and rainwater scouring was carried out at a rainfall of 50 mL / h. The scouring was carried out while the wind was blowing and the rain was scouring for 24 hours. The shear strength of the hot melt adhesive on the concrete floor was tested again with reference to GB / T7124-2008, and the data was recorded; at the same time, the area of the waterproof membrane lifted and the cracked area were recorded.
[0051] Table 1 Performance test table It can be seen from Application Examples 1-3 and Table 1 that the hot melt adhesive on the waterproof membrane of the present application has a high bonding effect on the concrete surface, and still has a high bonding stability under the simultaneous erosion of typhoons and rain, and is not prone to cracking or lifting.
[0052] From Application Example 1 and Comparative Application Examples 4-7 and Table 1, it can be seen that in Application Example 4, the polyimide fiber is replaced by an equal mass of glass fiber in the preparation process of the shellac-loaded fiber on the hot melt adhesive, and in Application Example 5, the polyimide fiber is replaced by an equal mass of polyimide fiber filament in the preparation process of the shellac-loaded fiber on the hot melt adhesive. Compared with Application Example 1, the shear strength of Application Examples 4 and 5 is smaller than that of Application Example 1, and the lifted area and cracked area are both larger than that of Application Example 1; this indicates that the rosin resin melt and silica gel particles on the surface of the polyimide fiber can absorb impurity particles on the concrete surface, thereby ensuring the bonding stability of the hot melt adhesive on the concrete surface.
[0053] In the preparation process of polyimide fiber of shellac-loaded fiber on hot melt adhesive in Application Example 6, silica gel particles were replaced with silica gel microparticles of equal mass. Compared with Application Example 1, the shear strength of Application Example 6 was smaller than that of Application Example 1, and the lifted area and cracked area were larger than those of Application Example 1. This indicates that the silica gel particles are not hydrophobicized and are easy to absorb rainwater, thus affecting the bonding effect of the hot melt adhesive on the concrete surface. Combined with the influence of wind, the waterproof membrane is easy to be lifted.
[0054] No zinc oxide whiskers were added to the filling particles in Application Example 7. Compared with Application Example 1, the shear strength of Application Example 7 was lower than that of Application Example 1, and the lifted area and cracked area were both larger than those of Application Example 1. This indicates that the needle-pierced structure of zinc oxide whiskers has a larger specific surface area, can better absorb hot melt adhesive, and is convenient for filling and attaching to the micropores on the concrete surface to drain the hot melt adhesive, thereby further improving the bonding effect between the hot melt adhesive on the waterproof membrane and the concrete surface.
[0055] From Application Example 1 and Comparative Application Examples 1-3 and Table 1, it can be seen that no shellac carrier fiber was added to the raw materials of Comparative Application Example 1. Compared with Application Example 1, the shear strength of Comparative Application Example 1 is smaller than that of Application Example 1, and the lifted-up area and cracked area are both larger than those of Application Example 1; this indicates that the addition of shellac carrier fiber can improve the bonding strength and flexibility of the hot melt adhesive, making it easier to resist the erosion of typhoon winds and rainwater, and less prone to cracking and lifting.
[0056] In comparative application example 2, the shellac-carrying fiber is replaced with shellac of equal mass in the raw materials. Compared with application example 1, the shear strength of comparative application example 2 is smaller than that of application example 1, and the lifted area and cracked area are larger than those of application example 1, which indicates that the addition of fibers can further improve the flexibility and strength of the waterproof membrane.
[0057] In comparative application example 3, the shellac carrier fiber is replaced with glass fiber of equal mass in the raw material. The average length of the glass fiber is 80 μm. Compared with application example 1, the shear strength of comparative application example 3 is less than that of application example 1, and the lifted area and cracked area are both larger than those of application example 1, which indicates that the glass fiber only has rigidity, poor flexibility, and cannot improve the bonding effect of the hot melt adhesive.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A hot melt adhesive for non-asphalt-based waterproofing membrane, characterized in that: The hot melt adhesive comprises the following raw materials in parts by weight: 70-100 parts of polymer polyol, 30-50 parts of isocyanate, 20-30 parts of acrylic resin, 20-30 parts of EVA, 10-20 parts of chain extender, 5-10 parts of compatibilizer, 5-15 parts of shellac carrier fiber, 10-20 parts of filling particles and 2-5 parts of antioxidant.
2. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 1, characterized in that: The shellac carrier fiber is prepared by bonding the surface of shellac particles with polycaprolactone melt and then bonding with polyimide fiber; the mass ratio of shellac particles, polycaprolactone melt and polyimide fiber is 1:0.3-0.6:1-2.
3. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 2, characterized in that: The polyimide fiber is prepared from polyimide fiber yarn, rosin resin melt and silica gel particles in a mass ratio of 1:0.05-0.1:0.1-0.
2.
4. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 3, characterized in that: The silica gel particles are prepared by treating silica gel microparticles with a silane coupling agent KH-570.
5. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 1, characterized in that: The filling particles are composed of carbon fibers, nano silicon dioxide and zinc oxide whiskers in a mass ratio of 1:0.5-1:0.1-0.
2.
6. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 1, characterized in that: The chain extender consists of dopamine and polyethylene glycol in a mass ratio of 1:1-3.
7. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 1, characterized in that: The compatibilizer is composed of maleic anhydride grafted EVA.
8. The hot melt adhesive for non-asphalt-based waterproofing membrane according to claim 1, characterized in that: The antioxidant is antioxidant 1010.
9. The method for preparing a hot melt adhesive for non-asphalt-based waterproofing membrane according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, weighing polymer polyol and isocyanate, mixing them evenly, heating them for reaction, then adding chain extender, and continuing the reaction to obtain a primary mixture; S2. Add acrylic resin, EVA, compatibilizer, fiber carrier shellac, filler particles and antioxidant to the primary mixture, mix and stir evenly, continue to react, and after defoaming, obtain the finished product.
10. A non-asphalt waterproofing membrane, characterized in that: The invention is made of a high-density polyethylene substrate and a hot-melt adhesive; the hot-melt adhesive is the hot-melt adhesive according to any one of claims 1 to 8 or the hot-melt adhesive prepared by the hot-melt adhesive preparation method according to claim 9.
